Treatment of eating disorders: voices from a ward. Issue 1 (1st January 2021) - Solhaug Storli, Cathrine; Alsaker, Sissel
ABSTRACT: Purpose: The purpose of this study is to explore and develop knowledge about treatment experiences of people suffering from severe eating disorders, by highlighting the patient's perspective in treatment. The study's issue is: "How do patients with severe eating disorders experience everyday hospital/in-hospital treatment, and how do they value the impact of their experiences in treatment?" Method: The study takes a qualitative approach, where patients wrote diaries that formed the data. There were 3 participants who wrote diaries twice a day for 2 weeks. In this study, thematic interpretative analysis of narrative data was used. Results and conclusion: The results of this study indicate that several health-related experiences emerged during treatment. The results show that the experiences of in-hospital treatment for severe ED are mostly characterized by experiences that might reduce the participants' sense of meaning. The study suggests new arenas (besides taking control over food/their bodies) for individual patients experienced mastery in their own recovery process.